Fintech empowerment for Malaysian women entrepreneur / Carolin Ann Enchas - Enchas, Carolin Ann (Corporate Communication Unit, UiTM Mukah Campus, 2024)
Over the past few decades, technological advancements have significantly expanded, leading to the widespread adoption of digital financial services, including mobile and internet-based transactions. This shift accelerated even more during the COVID-19 pandemic. The emergence of financial technology (fintech) in Malaysia is transforming opportunities for women entrepreneurs, equipping them with modern resources to attain financial independence and grow their enterprises. Fintech is enabling women by tackling the conventional obstacles they encounter in obtaining funding, enhancing financial literacy, and assisting them in creating supportive networks.